Lateral Canthotomy and Cantholysis in Operations Iraqi Freedom and Enduring Freedom: 2001–2011. Issue 1 (January 2019) - Jaksha, Alexandria F.; Justin, Grant A.; Davies, Brett W.; Ryan, Denise S.; Weichel, Eric D.; Colyer, Marcus H.
Abstract : Purpose: : To describe outcomes and associated ocular injuries of lateral canthotomy and cantholysis (LCC) as performed in combat ocular trauma. Methods: Data from the Walter Reed Ocular Trauma Database of patients requiring LCC during Operations Iraqi Freedom and Enduring Freedom was reviewed as a retrospective cohort. Primary outcome measures included final visual acuity (VA) and Ocular Trauma Score. Secondary outcome measures were associated injuries and timing of surgery. Results: Thirty-six LCCs were recorded on a total of 890 eyes (4.04 %) in the Walter Reed Ocular Trauma Database. Eighteen out of 36 eyes (50.00%) had a final VA of the affected eye of 20/200 or worse vision. From the initial available VA measured either at the time of injury or at Walter Reed Army Medical Center, 13 eyes (40.63%) had no change in VA, 15 eyes (46.88%) had improvement, and 4 (12.5%) had a decrease in VA (n = 32, data unavailable for 4 eyes). Ocular Trauma score 0–65 was noted in 14 (38.9%) and 66–100 (61.1%). Retinal detachment (6, 16.67%), optic nerve injuries (7, 19.44%), orbital fractures (20, 55.56%), and retrobulbar hematoma (25, 69.44%) were commonly associated injuries. Of the 36 LCC, 18 (50.00%) were performed as the first surgery performed at the combat support hospital, 13 (36.11%) as the second, 4 (11.11%) as the third, and 1 (2.78%) as the fourth. Conclusions: The largest subgroup of patients had an improvement in VA associated with performance of LCC; however, half of patients remained with a final VA of equal to or worse than 20/200 due to severe ocular trauma. Abstract : Most patients had improved vision when lateral canthotomy and cantholysis was performed during combat ocular trauma, but half of patients treated remained with a final visual acuity worse than 20/200 due to severe ocular trauma.